Multi-objective Functions in Grid Scheduling - Zafril Rizal, M Azmi; M. A., Ameedeen; Imran Edzereiq, Kamarudin (Springer International Publishing, 2015)
In order to fully utilize the Grid resources, an implementation of a good scheduling algorithm is greatly important. However, for a complex scheduler that aims to achieve high performance for more than one performance metrics, a suitable objective function should be carefully considered. This paper shows that a different objective function will have different affect to the Grid performance.